Development of Poetry Writing Guidebook Using Mind Mapping Model for Primary School Students - Mega Mutia; Beta Rapita Silalahi (PT Inovasi Pratama Internasional, 2022)
An important problem that is often faced by teachers in learning activities is choosing and determining appropriate learning materials or teaching materials in order to help students achieve competence. This study aims to develop a guidebook for writing poetry using the mind mapping model for fifth grade elementary school students, namely, (1) describing the profile of poetry, (2) describing the assessment of media experts and material experts on the prototype guidebook, and (3) describing the limited effectiveness test in class V students at SDN 105366 Sei Naga Lawan. This study uses research and development methods. This research is research that is used to produce certain products, and test the effectiveness of these products in class V students at SDN 105366 Sei Naga Lawan. Based on the results of this study, it can be stated as follows: (a) seen from the cover side of the book, students and teachers need an attractive design and are easy to carry everywhere, (b) seen from the content side, students and teachers need books that use standard language, simple, and communicative so that it makes it easier for students to learn it, (c) the dimensions of the book cover scored 90%, (d) the dimensions of the guidebook form scored 90, (e) the dimensions of the guidebook contents scored 98%. 3) The conclusion about the effectiveness test is limited to fifth grade students at SDN 105366 Sei Naga Lawan, the results of the research on writing narrative essays with guidebooks produce an average score of 95%.